2013
DOI: 10.1515/langcog-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to analysing static locative expressions

Abstract: As speakers, we are frequently called upon to specify the locations of objects and landmarks in our environment. However, despite the considerable body of work on spatial cognition and semantics (i.e. Levinson 1992, 1996, 2003; Tyler and Evans 2003; Herskovits 1986; Vandeloise 1986), there has been almost no research on the expression of location from a multimodal viewpoint: that is, how do speakers use gesture, as well as speech, to express object location? This paper reports on a filmed study of 10 English s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In the latter case humans programme the robot through language (Lauria et al 2002). Cross-disciplinary research has shown that spatial language is dependent on several contextual factors that are part of an agent's interaction with the environment through perception and other agents through dialogue, for example geometrical arrangement of the scene (Regier and Carlson 2001), the type of objects referred to and their interaction (Coventry et al 2001;Dobnik andKelleher 2013, 2014), visual and discourse salience of objects (Kelleher et al 2005), alignment in dialogue (Watson et al 2004;, and gesture (Tutton 2013) among others.…”
Section: Computational Modelling Of Spatial Languagementioning
confidence: 99%
“…In the latter case humans programme the robot through language (Lauria et al 2002). Cross-disciplinary research has shown that spatial language is dependent on several contextual factors that are part of an agent's interaction with the environment through perception and other agents through dialogue, for example geometrical arrangement of the scene (Regier and Carlson 2001), the type of objects referred to and their interaction (Coventry et al 2001;Dobnik andKelleher 2013, 2014), visual and discourse salience of objects (Kelleher et al 2005), alignment in dialogue (Watson et al 2004;, and gesture (Tutton 2013) among others.…”
Section: Computational Modelling Of Spatial Languagementioning
confidence: 99%